Evaluating Capital Budgeting Efficiency in Nepal’s Beverage Industry: A Comparative Analysis of Financial Performance and Investment Decision-Making - Shah, Ghanshyam Prasad; Kumar, Anil (NPRC Journal of Multidisciplinary Research, 2025)
Capital budgeting is a crucial financial planning process that helps organizations evaluate long-term investment projects to maximize profitability, with this study focusing on Nepal’s beverages industry by analyzing two companies—Sunrise Nepal Food & Beverages Pvt. Ltd. (SNFBPL) and Birgunj Pure Drinking Water Udyog (BPDWU). The primary objective was to assess capital budgeting techniques such as Net Cash Outlay (NCO), Net Present Value (NPV), and Internal Rate of Return (IRR), alongside reviewing financing sources, cost of capital, and tool effectiveness. Using comparative analysis and chi-square hypothesis testing, the study found that SNFBPL had a higher NCO and longer Payback Period (10.03 years) but a superior NPV (NPR 55.6 million) and Profitability Index (1.225), whereas BPDWU exhibited a better IRR (15.16%) and quicker payback (6.63 years), with SNFBPL’s lower cost of capital (11.26%) attributed to leverage. The findings highlight significant differences in NCO and NPV but not IRR, leading to recommendations such as optimizing cost of capital, boosting sales, and prioritizing NPV in decision-making. This study adds value by examining capital budgeting practices in Nepal’s emerging market, offering insights for financial planning in the beverages sector.